Pan-STARRS1 as pilot-survey for panoptic time-domain science. Issue Volume 12:Issue S325(2016) (30th May 2017) - Hernitschek, Nina; Rix, Hans-Walter; Sesar, Branimir; Schlafly, Edward F.
Abstract: For examining possibilities and challenges in doing science with multi-band and non-simultaneous data from upcoming surveys like LSST, the Pan-STARRS1 (PS1) 3π can be used as a pilot survey. This is especially important to explore the possibilities in detection and classification of variable sources within the first years of LSST's 10-year baseline. We had explored the capabilities of PS1 3π for carrying out time-domain science in a variety of applications. We had used structure function fitting as well as period fitting, to search for and classify high-latitude as well as low-latitude variable sources, in particular RR Lyrae, Cepheids and QSOs.